Effects of Center-Based Child Care on Disadvantaged Children: Evidence from a Randomized Research Design - Chris M. Herbst (Institute of Labor Economics (IZA), 2024)
This paper uses the random assignment of poor families to treatment and control conditions in the Comprehensive Child Development Program (CCDP) to isolate the causal effect of center-based child care enrollment on child well-being. Operating throughout the early-1990's, the CCDP demonstration aimed to improve child development and family functioning by offering those in the treatment group five years of high-quality child care along with case management. As a result, treated children were substantially more likely to be enrolled in center-based programs throughout the preschool-age years, and I use this variation to estimate the impact of center care on children's language and social skills as well as health. I uncover mixed results: more time spent in center-based settings improves language skills but reduces social skills in the short-run, and both effects fade-out for most children within one to two years. I also find that early center care use is strongly predictive of later Head Start enrollment, indicating that a more deliberate "family retention strategy" may be effective at lengthening children's exposure to high-quality early education.
Keywords: I21; J13; 330; child care; child development; maternal employment; instrumental variables